Writing for design professionals : a guide to writing successful proposals, letters, brochures, portfolios, reports, presentations, and job applications for architects, engineers, and interior designers - Kliment, Stephen A. (New York : W.W. Norton, 1998)
Written and oral communication plays a vital role in advancing design professionals' careers. Stephen Kliment spells out the various forms of writing that professionals need, including marketing and promotional materials and reports and project communications with clients.
Includes bibliographical references (pages 220-224) and index.
ARC
Keywords: Architectural services marketing -- United States; Engineering services marketing -- United States; Design services -- United States -- Marketing